INFLUENCE OF INFORMATION TECHNOLOGY AND EMPLOYEE ENGAGEMENT ON PERFORMANCE: A CASE STUDY AT THE MAGELANG BRANCH OF BPJS KETENAGAKERJAAN - Nadhiya Agustina; Suci Iriani Sinuraya; Joko Tri Nugraha (DIA: Jurnal Administrasi Publik, 2026)
Study these done for identify and analyze influence technology information and engagement employee to performance employees at the BPJS Ketenagakerjaan Magelang Branch. The data source is primary data obtained from distribution questionnaire to 30 respondents, and sources secondary based on journals, books, research previously, as well as literature others. Research this use method quantitative with data collection through sample fed up with make all over population become sample data supported by tools help statistical program SPSS version 30. Research results show if in a way partial (t-test), technology information and engagement employee influential in a way positive to performance employees. In simultaneous (F-test), variable technology information and engagement employee in a way together influential in a way significant to performance employees at the BPJS Ketenagakerjaan Magelang Branch. The R Square value shows 58.2% variation figure explained by variables technology information, engagement employees and performance employees. As for the rest 41.8 % is explained by other variables outside the model that are not investigated in this study.